2001
DOI: 10.1007/s002400100184
|View full text |Cite
|
Sign up to set email alerts
|

The effects of organ resection on rat urinary bladder carcinogenesis

Abstract: The effect of unilateral nephrectomy, orchiectomy or partial hepatectomy on the growth of chemically induced rat bladder tumors was investigated. Male F344 rats were treated with 0.05% N-butyl-N-(4-hydroxybutyl) nitrosamine (BBN) for 5 weeks, and surgical resection of one of these organs was performed 2 weeks after the completion of BBN administration. Histological evaluation of the bladder 24 weeks after the start of the experiment revealed that unilateral nephrectomy and orchiectomy significantly increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…One study found that unilateral orchiectomy actually promoted BBN induced bladder carcinogenesis in male rats (Saikawa et al 2001). Although these data seem contradictory to previous reports, the study noted that AR protein expression was higher following unilateral orchiectomy (Saikawa et al 2001). Thus, it is possible that despite orchiectomy, increased AR levels could compensate for decreased testosterone levels.…”
Section: Role Of Ar In Bladder Carcinogenesismentioning
confidence: 78%
“…One study found that unilateral orchiectomy actually promoted BBN induced bladder carcinogenesis in male rats (Saikawa et al 2001). Although these data seem contradictory to previous reports, the study noted that AR protein expression was higher following unilateral orchiectomy (Saikawa et al 2001). Thus, it is possible that despite orchiectomy, increased AR levels could compensate for decreased testosterone levels.…”
Section: Role Of Ar In Bladder Carcinogenesismentioning
confidence: 78%
“…The half-life was about one week (3 to 13 days) and the time to maximum concentration was between 30 minutes to 4 hours [60]. The first phase I/II study revealed 43% (13 of 30 patients) had PSA declines of 50% or greater [59]. In another important phase I/II study, 140 men with CRPC received increasing doses of enzalutamide (30-600 mg) and more than half of the patients had PSA declines (greater than 50%) [60].…”
Section: Enzalutamide (Mdv-3100)mentioning
confidence: 99%
“…Enzalutamide is an oral AR signaling inhibitor that not only blocks androgen binding to AR, with a 5-8 fold higher affinity compared to bicalutamide, but also prevents AR nuclear translocation, DNA binding, and coactivator recruitment [59]. The half-life was about one week (3 to 13 days) and the time to maximum concentration was between 30 minutes to 4 hours [60].…”
Section: Enzalutamide (Mdv-3100)mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, testicular castration (TC) can decrease BBN-induced bladder carcinogenesis 8,9 with a reduction in the CYP4B1 level resp on sible fo r mu tagenic activation of bladder carcinogens 10 . However, when TC applied after BBNinitiation TC enhances both BrdU-incorporation into the urothelium and development of preneoplastic and/or neoplastic lesions 11 .…”
Section: Introductionmentioning
confidence: 99%